"Ok Google, am I sick?": artificial intelligence, e-health, and data protection regulation (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The healthcare sector has been impacted by Artificial Intelligence systems for several years. This is certainly favoured by the constant development of technologies based on sophisticated machine learning and techniques that are able to find complex patterns in data. However, several critical issues hinder AI's definitive affirmation: from a lack of clinical studies that can demonstrate its reliability and greater effectiveness with respect to traditional systems, to the criticalities related to the attribution of responsibility in the event of medical errors. In particular the application of data protection regulation to this specific scenario needs to be carefully evaluated. The correct management of this technology, through legal intervention in preventing possible dehumanization, plays a crucial role. This paper aims to investigate the impact of technologies based on AI in the healthcare sector, with particular attention to personal data protection issues.
Keywords: Artificial Intelligence; e-Health; Privacy; Data protection; Automated decision making